Korelasi Perspektif Standar Rasio Likuiditas, Solvabilitas Dan Rentabilitas Koperasi Terhadap Kinerja Keuangan Primer Koperasi Kartika Ardagusema Cimahi - Maulana, Arman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
Primary Cooperative Kartika Ardagusema is one type of business entity engaged in the field of all-businesscooperatives whose scope is all civil servants. In this research, the object of research is the financial ratioto the financial performance of cooperatives that is influenced by liquidity, solvency and profitability. Thehypothesis proposed in this study is liquidity, solvency and profitability partially and simultaneously whichhas an influence on financial performance. The types and sources of data used in this study are primarydata that is data obtained through direct interviews with cooperatives and by distributing questionnairesto cooperative members. Secondary data is data in the form of publications from cooperatives oncooperative organizational structures and cooperative activities. In analyzing the data that has beencollected the author uses quantitative analysis methods by using the correlation analysis formula. Fromthese calculations using SPSS 20.00, the effect of each independent variable on the dependent variable isobtained, as can be seen between the liquidity of the significance value of 0.028 <0.05, solvability 0.559<0.05 and rentability 0.362 <0.05, which means there is a correlation significant.